STRATEGI DAKWAH KULTURAL MUHAMMADIYAH DI ERA DIGITAL - Lely Agustyawati (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2022)
Muhammadiyah is an Islamic movement based on the Qur'an and Sunnah with a tajdid movement attached to itself which is the identity of Muhammadiyah and has a mission of amar ma'ruf nahi munkar which means competing for good in all areas of life. As an effort to make Islam as rahmatan lil al-'alamin, namely as the mercy of the entire universe, Muhammadiyah various approaches and strategies of da'wah, including through cultural da'wah. Cultural da'wah as an approach and strategy of da'wah as an effort to actualize Islamic teachings in the midst of cultural and social dynamics. In the change of a community that runs gradually according to the conditions of the local community. The concept of Muhammadiyah's cultural da'wah is basically based on two aspects, including aspects of dynamism and purification. First, the dynamics of considering the potential and tendency of humans as cultural beings, to make efforts so that culture can bring progress and enlightenment to human life. Second, purification tries to avoid the preservation of the existing culture, which is evident in terms of Islamic teachings contaminated with shirk, superstition, heresy and khurafat.